2013
DOI: 10.1158/1538-7445.am2013-2243
|View full text |Cite
|
Sign up to set email alerts
|

Abstract 2243: Clonogenic 3D high throughput screening in mutant KRAS dependent cancer cells - a chemogenomic approach.

Abstract: Activating KRAS mutations are oncogenic and prevalent in multiple tumor types, being found in as high as 90% of pancreatic carcinomas and 50% of colorectal carcinomas. In spite of its attractiveness for therapeutic intervention to date no KRAS-targeted drug therapies have been approved. Most of the reported mutant KRAS directed cellular screening efforts utilize 2-dimensional assays. Because mutant KRAS driven tumor cell lines are much more strongly dependent on activated K-Ras signaling for anchorage independ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Recently, investigators at Abbott Laboratories developed a soft agar colony formation assay that can be adapted to high-content screening, thereby bringing an important secondary assay to the forefront of primary phenotypic screening [47]. This 384-well 3D assay then opened the door for other big pharma screening projects such as the one by Sanofi-Aventis which involved screening 300,000 compounds on five different Kirsten RAt Sarcoma viral oncogene homologue (the most highly mutated and undruggable oncogene in human cancers) (KRAS)-dependent cancer cell lines grown in 3D ECM to identify pathways, targets or chemical matter with selective KRAS antitumor activity [48]. Researchers at Novartis have taken the 384-well colony formation assay even further, mixing normal colon fibroblasts together with colorectal carcinoma cells to achieve therapeutic indices of experimental test compounds [24].…”
Section: Hts Ecm Assaysmentioning
confidence: 99%
“…Recently, investigators at Abbott Laboratories developed a soft agar colony formation assay that can be adapted to high-content screening, thereby bringing an important secondary assay to the forefront of primary phenotypic screening [47]. This 384-well 3D assay then opened the door for other big pharma screening projects such as the one by Sanofi-Aventis which involved screening 300,000 compounds on five different Kirsten RAt Sarcoma viral oncogene homologue (the most highly mutated and undruggable oncogene in human cancers) (KRAS)-dependent cancer cell lines grown in 3D ECM to identify pathways, targets or chemical matter with selective KRAS antitumor activity [48]. Researchers at Novartis have taken the 384-well colony formation assay even further, mixing normal colon fibroblasts together with colorectal carcinoma cells to achieve therapeutic indices of experimental test compounds [24].…”
Section: Hts Ecm Assaysmentioning
confidence: 99%
“…Pancreatic cancer cells often display aberrations of mitochondrial dynamics in favor of mitochondrial fission [1,6], where these organelles take on a fragmented appearance, which appears to be a KRAS-dependent phenomenon [7]. We previously demonstrated that this overactive mitochondrial fission could be therapeutically targeted by disrupting Drp1, increasing expression of Mfn2 genetically, or with the use of leflunomide [1].…”
Section: Introductionmentioning
confidence: 99%